al-Numur fi al-yawm al-'ashir - Tamir, Zakariya (London : Riyad al-Rayyis Book Ltd, 1994)
The short, tightly told title story of this collection, Tigers on the Tenth Day, is an allegory that recounts with control how even the strongest of us can be gradually broken and tamed by those who wield the whip of power. Most of Zakaria Tamer's stories deal with man's inhumanity to man -- likewise to woman -- the oppression of the poor by the rich and of the weak by the strong. The political and social problems of his own country, Syria, and of the contemporary Arab world, are reflected in the stories and sketches in the sharply satirical style typical of his writing. -- From http://www.interlinkbooks.com (Oct. 24, 2012).
Title on t.p. verso: The tigers on the 10th day.
Short stories.
Keywords: Short stories, Arabic -- Syria -- 20th century; Short stories, Arabic -- 20th century; Syria -- Social conditions -- Fiction; Syria -- Politics and government -- Fiction; Syria -- Social life and customs -- Fiction; Arab countries -- Social conditions -- Fiction; Arab countries -- Politics and government -- Fiction; Arab countries -- Social life and customs -- Fiction